A Comparative Study of the Innervation of the Gum: (Section of Odontology) - Stewart, D. (1939)
In this paper we give a comparative study of the innervation of the connective tissues of the gum underlying the epithelium. Our material was taken from carnivores, rodents, insectivores and men. The fibres form superficial and deep plexuses and leashes, and specialized nerve-endings are also present. The types of specialized nerve-endings seen have been:— (1) Coils which are situated either in the intra-papillary zone of the deeper connective tissue. (2) Ruffini-like nerve-endings and convoluted fibres the presence of which in the gum has not been previously described.